Decellularized colorectal cancer matrix as bioactive microenvironment for in vitro 3D cancer research. Issue 8 (27th February 2018) - Piccoli, Martina; D'Angelo, Edoardo; Crotti, Sara; Sensi, Francesca; Urbani, Luca; Maghin, Edoardo; Burns, Alan; De Coppi, Paolo; Fassan, Matteo; Rugge, Massimo; Rizzolio, Flavio; Giordano, Antonio; et al.
Abstract : Three‐dimensional (3D) cancer models are overlooking the scientific landscape with the primary goal of bridging the gaps between two‐dimensional (2D) cell lines, animal models and clinical research. Here, we describe an innovative tissue engineering approach applied to colorectal cancer (CRC) starting from decellularized human biopsies in order to generate an organotypic 3D‐bioactive model. This in vitro 3D system recapitulates the ultrastructural environment of native tissue as demonstrated by histology, immunohistochemistry, immunofluorescence and scanning electron microscopy analyses. Mass spectrometry of proteome and secretome confirmed a different stromal composition between decellularized healthy mucosa and CRC in terms of structural and secreted proteins. Importantly, we proved that our 3D acellular matrices retained their biological properties: using CAM assay, we observed a decreased angiogenic potential in decellularized CRC compared with healthy tissue, caused by direct effect of DEFA3. We demonstrated that following a 5 days of recellularization with HT‐29 cell line, the 3D tumor matrices induced an over‐expression of IL‐8, a DEFA3‐mediated pathway and a mandatory chemokine in cancer growth and proliferation. Given the biological activity maintained by the scaffolds after decellularization, we believe this approach is a powerful tool for future pre‐clinical research and screenings. Abstract : With this research work we demonstrated that detergent enzymatic treatment is a good decellularization method to obtain acellular scaffold from both healthy and tumor human biopsies. Our protocol allows preserving original structure, ultrastructure, architecture, and protein composition. Moreover, peptides and small molecules retained in the decellularized matrices maintained biological activity and effect, nominating this technique an interesting approach to overcome obsolete 2D culture models and to perform more relevant in vitro 3D clinical screening and drug delivery assays.